Connected Sahrawi refugee diaspora in Spain: Gender, social media and digital transnational gossip. (October 2020) - Almenara-Niebla, Silvia; Ascanio-Sánchez, Carmen
While there is increasing scholarly attention given to the impact of digital technologies on forced migration, the points of view and situated experiences of refugees living in the diaspora are understudied. This article addresses Sahrawis refugee diasporas, which have close ties with the Sahrawi political cause. Resulting from the unresolved Western Sahara conflict, Sahrawi forced migrants are at the eye of one of the world's most protracted refugee situations. While most Sahrawis live in refugee camps in Algeria, some Sahrawis have managed to travel onwards. Social media allows those living elsewhere to maintain connections with contacts living in their original refugee camp. However, Facebook has become a complex environment, particularly for Sahrawi women. Gendered mechanisms of control, such as digital transnational gossip, result in a paradoxical politics of belonging: these women simultaneously desire to keep in touch but do not want to become a subject of gossip. From narratives of Sahrawi young women based in Spain gathered through interviews between 2016 and 2018, as well as a specific Facebook campaign and fan page, the focus is on strategies Sahrawi women develop to avoid and confront digital transnational gossip.